Le contexte revisité - Catherine Kerbrat-Orecchioni (Corela)
In this paper we’ll come back to some problems raised by the notion of context, considered in a pragmatic and interactional perspective. From the case of speech acts (especially wishes), we’ll see that their description in the linguistic system requires to take into account some elements of context, which is still more indispensable when dealing with samples of discourse, in order to describe the emergence of some particular « effets de sens ». From the case of mediatic debates, we’ll focus on the fact that context is not the same for the different participants to the speech event and for the analyst who has to describe it. Finally we’ll raise the question of what the tasks of the analyst, confronted to such diverse points of view, « ideally » consist in.